CONSUMERS PREFERENCES TEST OF SAMBAL LEMEA THE UNIQUE FOOD OF REJANGNESE AND CHANGED PRODUCTS IN VARIOUS STORAGE TEMPERATURE - Yantri Nuryani; Laili Susanti; Kurnia Herlina Dewi (Jurnal Agroindustri, 2012)
Lemea is one of the unique food of Rejangnese which  made from bamboo shoots  and fermented fish.  This research is  aimed to find the effect of processing and storage temperature on moisture content, pH, total microbial and consumers preferences ( color, aroma, and taste) of sambal lemea. This research carried out by using CRD with two factors namely processing (pots and bamboo) and storage temperature (room temperature and refrigerator). The results showed that the treatment gives significant effect on moisture content, pH and the level of preference (color, aroma and flavor). While the temperature did not show significant differences.  Sambal lemea which cooked in bamboo has the highest preferences score on color, aroma and flavor on days 0 and 7.